In Vitro Study of Antibacterial Activity of Patindis Leaf Extract (Urophyllum arboreum) and Microneedle Acne Patch against Propionibacterium acnes and Staphylococcus aureus - Hayatun Izma; Deni Setiawan; Putri Helena Junjung Buih; Khoirunnisa Muslimawati; Naila Azizah; Mahfuzatul Ajmi (Universitas Lambung Mangkurat, 2026)
Acne vulgaris is a cutaneous disorder associated with Propionibacterium acnes and Staphylococcus aureus. This study investigated the antibacterial activity of patindis leaf extract (Urophyllum arboreum) and its microneedle acne patch against both bacteria. The extract was prepared from dried simplicia by maceration using 96% ethanol. Phytochemical screening was conducted using test-tube methods. Antibacterial testing included determination of inhibition zone diameter using the well-diffusion method, as well as the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Clindamycin 1% was used as a positive control, while 20% DMSO and microneedle patches without extract served as negative controls. The U. arboreum leaf extract contained flavonoids, alkaloids, saponins, condensed tannins and terpenoids. At concentrations of 1.25%, 2.5%, and 5%, the extract produced inhibition zones of 12.368, 14.693, 18.403 mm against P. acnes and 14.523, 17.408, 18.840 mm against S. aureus, respectively. The MIC and MBC values against both bacteria were 0.625%. The microneedle acne patch formulations produced inhibition zones of 9.196 mm (F1), 10.140 mm (F2), and 10.713 mm (F3) against P. acnes, but showed no activity against S. aureus. These results indicate that the microneedle acne patch containing U. arboreum leaf extract has potential as an alternative topical antibacterial agent.